2005
DOI: 10.1186/1477-7819-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Neck dissections: radical to conservative

Abstract: Background: Neck dissection is an important surgical procedure for the management of metastatic nodal disease in the neck. The gold standard of neck nodal management has been the radical neck dissection. Any modification in the neck dissection is always compared with this standard. Over the last few decades, in order to alleviate the morbidity of radical neck dissection, several modifications and conservative procedures have been advocated. These procedures retain certain lymphatic or non-lymphatic structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…Nowadays, attempts are being made to replace MRND with SND for early node positivity 37 . It is possible that in the future, SND combined with adjuncts such as radiotherapy or chemotherapy will become the standard of care for advanced nodal disease 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, attempts are being made to replace MRND with SND for early node positivity 37 . It is possible that in the future, SND combined with adjuncts such as radiotherapy or chemotherapy will become the standard of care for advanced nodal disease 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the previous few decades, the mainstay for neck dissection has shifted from radical surgery to a more conservative modality [ 23 ]. The work of Bajwa et al [ 24 ] suggested that levels I to III selective neck dissection (SND) is effective management of the cN0 neck condition in patients with oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Head and neck cancer (HNC), including the oral cavity, pharynx, and larynx, is the sixth most common malignant tumor worldwide 1 , 2 . Such cancers are mainly caused by consuming alcohol and smoking tobacco, resulting in genomic mutations 3 .…”
Section: Introductionmentioning
confidence: 99%